Formalization of decision-making procedures regarding the extension of the operation term of railway rolling stock in the conditions of post-war development of Ukraine - Holub, Halyna; Haidenko, Oles (Technology transfer: fundamental principles and innovative technical solutions, 2023)
Today, the vast majority of the railway transport fleet in Ukraine has reached the end of its service life, set by the manufacturer. One of the ways to solve the problem of aging rolling stock, along with the purchase of new wagons and locomotives, remains the extension of the service life of passenger wagons due to the restoration of their resource during appropriate repairs. However, the extension of the service life of rolling stock in Ukraine is regulated by a large number of documents (more than a dozen). Since information is scattered in various sources, the need to consider many criteria regarding the possibility of extending the service life of various types of railway rolling stock units creates certain difficulties in perceiving information and takes time to make a decision on the appointment of the necessary type of repair. One of the solutions to the problem of decentralization of the regulatory framework, along with its change, is its formalization for further development of automated decision-making systems in this area. The paper proposes the classification of passenger wagons of locomotive traction (as the most difficult case) by type and place of production from the point of view of the issue of continuing operation beyond the period established by the manufacturer. An algorithm has been developed for the exact calculation of the difference between dates (construction, repair history, and the maximum period of operation), ensuring compliance with regulatory documents, and based on it, software that allows to determine the existence of grounds for extending the term as quickly as possible in the conditions of technical diagnostics using a smartphone operation of the load-bearing structures of locomotive traction passenger wagons and calculate the type of repair that must be scheduled according to the calendar period